(untitled) (Research, Society and Development, 2020)
Brazilian cities have undergone profound changes in soil cover by the accelerated process of urbanization in recent centuries. The growth process of the cities decreased the plant areas, which act essentially in the thermal comfort and well-being of the population, generating changes in thermal sensations. It is in this context that this article is inserted, with the objective of analyzing the Heat Index (CI), Thermal Discomfort Index (RTD), Temperature and Humidity Index (UTI) and the climatological variables that are related to human thermal comfort. This study was carried out in the city of Barbalha, located in the Metropolitan Region of Ceará. Historical data from the National Institute of Meteorology - INMET were used for the period 2016 to 2019. From the methodology of Steadman (1979) and Thom (1959) the thermal comfort indexes were calculated using excel software. The results showed that throughout the study period, high temperatures occurred in the municipality, in addition to high values of HF, RTD and UTI, characterizing the municipality as thermally uncomfortable.